Change Management and its Impact on Organisational Performance: Empirical Evidence from an Oil and Gas Firm - Choy, May Yi (2016)
Despite the profuse output of academic literature and practitioner guidance on change management, the reportedly low success rates of many change programs prove that successfully delivering on what is originally intended to scales of time, cost and performance remains a major issue and pertinent business challenge to many executives and organisations today. Part of the problem that makes managing change difficult is the fact that there is little consensus on what factors most influence change efforts as organisations are dynamic and complex entities in reality, constantly evolving with time. The relationship between individual factors, organisational factors, change processes and organisational performance has been a key theme in change management literature. A review of literature has also revealed the need for more empirical research into the field application of change management practices and their effectiveness. This study seeks to address the shortfall of research in this area by investigating the influence and impact of individual factors, organisational factors and change processes on organisational performance which is measured in terms of two attitudinal job outcomes commonly studied in change research, i.e. employee job satisfaction and affective commitment. The association between change management and organisational performance in the context of the energy industry is also an area that has not been explored extensively. Change management is an area of industry relevance and importance given the high risk nature of the business. This study gathers empirical evidence from an oil and gas firm based in Malaysia. The study collected data from 101 respondents (21% of targeted population; 84.20% response rate) by means of a structured questionnaire. The data is subsequently analysed using SPSS version 20.0. Results indicated that these variables do impact organisational performance, with individual factors being the area where the selected organisation is most effective, followed by organisational change processes and lastly organisational factors. Organisational factors particularly reinforcing mechanisms reported the highest correlation to job satisfaction which indicates that job satisfaction is greatly influenced by reinforcing mechanisms. Correlation analysis also finds evidence supporting positive significant relationships between individual factors, organisational factors, change processes and organisational performance; consistent with earlier change management research. Leadership attributes, organisational diagnosis and change readiness and change preparation and alignment reported the highest correlation with organisational performance. Reinforcing mechanisms, organisational diagnosis and change readiness and change implementation reported the highest correlation with employee job satisfaction. The findings from this study have important implications and recommendations for the selected organisation and change practitioners in general. Of key importance is the need to integrate both soft and hard approaches in managing change with simultaneous focus on both; and prompt engagement of the workforce prior to the introduction of the change. To leverage on the reportedly high affective commitment of the workforce, it is also recommended that “insourcing” be considered, of establishing a pool of individuals trained to manage change effectively within the organisation as a means of employee engagement whilst building the internal capabilities of the organisation. Other recommendations include developing a formal change management framework to work to for all future major organisational changes with change readiness reviews being a key element in the framework; and demonstrating and communicating progress throughout the change effort. Change efforts can exert a heavy toll on both human and economic perspectives of the firm. Organisations can reduce and limit these costs by learning from past experiences and continuously improving future change efforts. Aside from providing insights to the interactive effects of these factors, it is hoped that this study will be a springboard for future research aimed at demonstrating the important role of these factors towards achieving successful change management and consequently enhanced organisational performance in the context of the energy industry.